2022
DOI: 10.3390/nu14030452
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ferrous Bisglycinate and Folinic Acid in the Control of Iron Deficiency in Pregnant Women: A Randomized, Controlled Trial

Abstract: Iron deficiency in pregnancy is a major public health problem that causes maternal complications. The objective of this randomized, controlled trial was to examine the bioavailability, efficacy, and safety of oral ferrous bisglycinate plus folinic acid supplementation in pregnant women with iron deficiency. Subjects (12–16 weeks of gestation, n = 120) were randomly allocated to receive oral iron as ferrous bisglycinate (equiv. iron 24 mg) in supplement form with folinic acid and multivitamins (test group, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Furthermore, Bumrungpert et al showed that ferrous bisglycinate 30 mg was as effective as 120 mg of ferrous sulfate in preventing IDA and with more persistent correction of ferritin levels after a six-month follow-up. 9 The chelated iron preparation improved hematological parameters, iron absorption, quality of life, and birthweight in iron-deficient pregnant women compared to ferrous fumarate. 9 A comparison of a few previously done studies with ferrous bis-glycinate and the present one is depicted in (Table 1).…”
Section: Good Very Goodmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Bumrungpert et al showed that ferrous bisglycinate 30 mg was as effective as 120 mg of ferrous sulfate in preventing IDA and with more persistent correction of ferritin levels after a six-month follow-up. 9 The chelated iron preparation improved hematological parameters, iron absorption, quality of life, and birthweight in iron-deficient pregnant women compared to ferrous fumarate. 9 A comparison of a few previously done studies with ferrous bis-glycinate and the present one is depicted in (Table 1).…”
Section: Good Very Goodmentioning
confidence: 99%
“…9 The chelated iron preparation improved hematological parameters, iron absorption, quality of life, and birthweight in iron-deficient pregnant women compared to ferrous fumarate. 9 A comparison of a few previously done studies with ferrous bis-glycinate and the present one is depicted in (Table 1).…”
Section: Good Very Goodmentioning
confidence: 99%
See 3 more Smart Citations